Handelinge se uitbeelding van die rol van vroue in die vroeë kerk - Howes, Llewellyn (HTS teologiese studies, 2005)
Acts and the role of women in the early churchThe aim of this article is to determine what the role of women in the church of the first century was according to Acts. Amongst other things it pertains to the situation of women within the community of believers on a daily basis. It not only includes their contribution to faith services and the faith community as a whole, but also how the faith community perceived them. What part did they play and what positions of leadership did they hold? Did their gender exclude them from exercising certain leadership roles? What was the gender-specific view of Christians? Establishing the historicity of every pericope in Acts is not the main aim. However, the article subscribe to the historicity of the overall picture of the role women played in the early church.